(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2003)
The openness of consciousness, particularly pivotal to Sartre’s early philosophy, gives immense difficulty to those who wish to give a comprehensive account of human nature. In this paper I note the treatment of human awareness of the world in some current theories: The issue (as Merleau-Ponty pointed out) is one of giving due weight both to the creativity of consciousness – its ordinary productivity – and to the connectedness of awareness to the events of the world. This dual structure of openness has not been fully captured by contemporary theories.